Transnational marketing and transnational consumers - Sirkeci, Ibrahim (SpringerBriefs in business, 2013)
Transnational Marketing and Transnational Consumers are becoming increasingly common in today's globalizing and fast moving world of business. This book presents a fresh perspective focusing on the transnational character of organizations and firms while underlining the importance of the transnationality of marketing strategies for success. At the same time, it introduces the novel concepts of Transnational Consumers and Transnational Mobile Consumers which take into account the increasing human mobility and its implications for marketing success. This book gives flesh to the ever popular shorthand "glocal" referring to strategies thinking globally but acting locally. This is the reality of current business environment where the norm is fast mobility of goods, services, finance, and consumers.